1s2p resonant inelastic X‐ray scattering combined dipole and quadrupole analysis method. (29th November 2016) - Bagger, Alexander; Haarman, Ties; Puig Molina, Anna; Moses, Poul George; Ishii, Hirofumi; Hiraoka, Nozomu; Wu, Yu-Han; Tsuei, Ku-Ding; Chorkendorff, Ib; De Groot, Frank
Abstract : An investigation into when RIXS measurements bring extra information compared with XAS is presented. Two models are used to analyse the RIXS data: an exciton model and a continuum model, which describe the quadrupole and dipole excitations, respectively. Abstract : In this study an analysis strategy towards using the resonant inelastic X‐ray scattering (RIXS) technique more effectively compared with X‐ray absorption spectroscopy (XAS) is presented. In particular, the question of when RIXS brings extra information compared with XAS is addressed. To answer this question the RIXS plane is analysed using two models: (i) an exciton model and (ii) a continuum model. The continuum model describes the dipole pre‐edge excitations while the exciton model describes the quadrupole excitations. Applying our approach to the experimental 1 s 2 p RIXS planes of VO2 and TiO2, it is shown that only in the case of quadrupole excitations being present is additional information gained by RIXS compared with XAS. Combining this knowledge with methods to calculate the dipole contribution in XAS measurements gives scientists the opportunity to plan more effective experiments.